Reliability analysis of 20 kV electric power distribution system based on SAIFI, SAIDI, CAIDI, MAIFI, ASAI and ASUI at PT. PLN Rayon Samalanga - Iqbal, Muhammad (Geuthèë Institute, 2024)
The reliability index of the distribution system is a measure of the system's ability to continuously supply electrical energy to loads over a specific period and under certain conditions. PT. PLN (Persero) Rayon Samalanga, as the electricity service provider in Bireun Regency, adheres to service standards in accordance with SPLN 59:1985 and the IEEE Reliability Index standard 1366-2003. This research analyzes the reliability level of PT. PLN (Persero) Rayon Samalanga's distribution network on six (6) feeders: feeder SL-1, feeder SL-2, feeder SL-3, feeder SL-4, feeder SL-5, and feeder SL-6. The reliability index calculation is based on the estimated failure rate (λ) and the estimated interruption duration (U) for each installed component. The calculation results show that the distribution lines of PT. PLN (Persero) Rayon Samalanga are categorized as reliable according to SPLN 59:1985 and the IEEE Reliability Index standard 1366-2003, with the highest reliability index on feeder SL-4 at SAIFI = 2.04 times/failure; the best SAIDI value is on feeder SL-3 with SAIDI = 2.06852 hours/year; the best CAIDI value is on feeder SL-3 with CAIDI = 0.21 times/failure; the best MAIFI value is on feeder SL-2 with MAIFI = 14.82 times/customer; the best ASAI value is on feeder SL-3 with ASAI = 0.99999684, and the best ASUI value is on feeder SL-2 with ASUI = 0.0000081